Análise numérica de pilares mistos de aço e concreto tubulares circulares com concreto de alto desempenho - Gomes, Harlley Davidson (2015)
Steel and concrete composite columns have been significantly employed in civil construction, mainly in countries in North America, Europe and Asia. Composite columns with concrete of normal strength, in other words, with cylinder strength between 20 and 50 MPa, are addressed by the main design codes. In Brazil, the standards ABNT NBR 8800:2008 and ABNT NBR 16239:2013 rule the dimensioning of steel and concrete tubular composite columns. Both standards reference the ABNT NBR 6118:2014 when dealing with matters related to the concrete’s structural resistance that incorporates the use of high strength concrete, which justifies the need for research works dealing with composite columns with high strength concrete. In the present study, numerical models were elaborated to simulate both normal and high strength concrete-filled circular tubular columns. After the validation of the numerical models with literature’s experimental results, an extensive parametric analysis was performed in order to assess the influence of geometric parameters (length, diameter and thickness of the steel tube) and material parameters such as the concrete resistance. Columns under normal and eccentric loads were analyzed and the numerical results were confronted with the prescriptions of the standards EN 1994-1-1:2004, ANSI/AISC 360-05:2010 and ABNT NBR 8800:2008. The viability of the usage of the standards’ equations in the calculations of the compressive strength of high strength concrete-filled tubular circular composite columns was verified. The analysis of the resistance to eccentric loading of these columns has led to the conclusion that the ANSI/AISC 360-05:2010 code leads to over-conservative results, while the ABNT NBR 8800:2008 conducts to results that are closer to the numerical ones, despite being against safety in some cases. The EN 1994-1-1:2004 presented, mostly, results that were contrary to safety.